Pendampingan Branding, Packaging, dan Digital Marketing Tingkatkan Penjualan Madu Kelulut Desa Tuwung - Yuliana, Yuliana; Agnestisia, Retno; Saputra, Rizki Rachmad; Pasaribu, Marvin Horale (Universitas Islam Indonesia, 2025)
Tuwung Village, located in the Kahayan Tengah District, Pulang Pisau Regency, Central Kalimantan, has significant potential in managing social forestry land to support food security. The local community, organized in the Social Forestry Business Group (KUPS), has successfully cultivated 120 hives of stingless bees (Trigona sp.), with monthly production capacity of up to 350 mL per hive. Although honey production is abundant, its sales remain very limited due to a marketing strategy that relies solely on word-of-mouth promotion. Therefore, this community service activity was introduced to provide guidance to KUPS Madu Kelulut on branding, product packaging, and digital marketing. With an attractive brand, high-quality packaging, and the right marketing strategy, it is hoped that the stingless bee honey business can become more competitive in a market already saturated with similar products. This community service program involved several stages, including preparation, implementation, and evaluation. The activity was carried out on July 9, 2024, with 40 participants. The evaluation results indicated an 81.25% increase in participants' understanding of branding, product packaging, and digital marketing. Furthermore, the participants successfully created the brand